2019
DOI: 10.3390/ma12111874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitin Nanofibrils on Biocompatibility and Bioactivity of the Chitosan-Based Composite Film Matrix Intended for Tissue Engineering

Abstract: This paper discusses the mechanical and physicochemical properties of film matrices based on chitosan, as well as the possibility of optimizing these properties by adding chitin nanofibrils. It is shown that with the introduction of chitin nanofibrils as a filler, the mechanical stability of the composite materials increases. By varying the concentration of chitin nanofibrils, it is possible to obtain a spectrum of samples with different bioactive properties for the growth of human dermal fibroblasts. Film mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…One of the most commonly used series for the estimation of p (x) is the Schlömlich expansion, used with good results by Doyle. (19) Doyle considers it sufficient to take only the first two terms of each series. With what: (20) And found that for x> 20 and taking logarithms could express p (x) as:…”
Section: Integral Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most commonly used series for the estimation of p (x) is the Schlömlich expansion, used with good results by Doyle. (19) Doyle considers it sufficient to take only the first two terms of each series. With what: (20) And found that for x> 20 and taking logarithms could express p (x) as:…”
Section: Integral Methodsmentioning
confidence: 99%
“…The great variety of applications of chitosan in the field of biomaterials is due to its excellent properties when interacting with the human body: bioactivity [7], antimicrobial and antifungal activity [8,9], immunostimulation [10], chemotactic action, enzymatic biodegradability, mucoadhesion and epithelial permeability [11] which supports the adhesion and proliferation of different cell types [11][12][13]. With the above properties, CHI derivatives serve a broad range of applications and these materials have advanced at a dramatic pace into many fields, including skin, wound and burn management [14][15][16]; drug delivery and pharmaceutical applications [17][18]; tissue engineering [19][20][21]; dentistry [22][23][24]; plant science and agriculture [25,26]; veterinary science [27,28]; cosmetics and cosmeceutical [29,30]; food and nutraceuticals [31,32]; and paper industry [33], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that chitosan and chitin can be used in a variety of applications in tissue engineering (Yilgor et al., 2009 ; Liu et al., 2016 ; Pangon et al., 2016 ; Islam et al., 2017 ; Ahsan et al., 2018 ). They can be designed into a variety of structures such as gels, membranes nanofibers, nanoparticle and sponges (Singh et al., 2017 ; Smirnova et al., 2019 ; Zubillaga et al., 2020 ). In combination with properties such as its good biocompatibility, biodegradability, nontoxic, anti-inflammatory, adhesion, antibacterial and nerve protection, chitosan can be made into a suitable candidate for growth factors delivery (Rajam et al., 2011 ).…”
Section: Applications Of Natural Polysaccharides In Tissue Engineerinmentioning
confidence: 99%
“…Until now, there have been different proposals of skin-like substitutes in an attempt to reproduce several aspects of real human skin, but, for many reasons, they are not considered as perfect human skin alternatives [ 1 ]. In most cases, living cells are cultured in an artificial scaffold, which means that the skin is difficult to manage and affects its costs and expiry date [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%